Panchromatic Sequentially Cast Ternary Polymer Solar Cells. Issue 4 (29th November 2016) - Ghasemi, Masoud; Ye, Long; Zhang, Qianqian; Yan, Liang; Kim, Joo‐Hyun; Awartani, Omar; You, Wei; Gadisa, Abay; Ade, Harald
Abstract : A sequential‐casting ternary method is developed to create stratified bulk heterojunction (BHJ) solar cells, in which the two BHJ layers are spin cast sequentially without the need of adopting a middle electrode and orthogonal solvents. This method is found to be particularly useful for polymers that form a mechanically alloyed morphology due to the high degree of miscibility in the blend.